Malnutrition and Its Determinants Are Associated with Suboptimal Cognitive, Communication, and Motor Development in Tanzanian Children. Issue 12 (7th October 2015) - Sudfeld, Christopher R; McCoy, Dana Charles; Fink, Günther; Muhihi, Alfa; Bellinger, David C; Masanja, Honorati; Smith, Emily R; Danaei, Goodarz; Ezzati, Majid; Fawzi, Wafaie W
Abstract: Background: A large volume of literature has shown negative associations between stunting and child development; however, there is limited evidence for associations with milder forms of linear growth faltering and determinants of malnutrition in developing countries. Objective: The objective of this study was to assess the association between anthropometric growth indicators across their distribution and determinants of malnutrition with development of Tanzanian children. Methods: We used the Bayley Scales of Infant Development III to assess a cohort of 1036 Tanzanian children between 18 and 36 mo of age who were previously enrolled in a neonatal vitamin A trial. Linear regression models were used to assess standardized mean differences in child development for anthropometry z scores, along with pregnancy, delivery, and early childhood factors. Results: Height-for-age z score (HAZ) was linearly associated with cognitive, communication, and motor development z scores across the observed range in this population (all P values for linear relation < 0.05). Each unit increase in HAZ was associated with +0.09 (95% CI: 0.05, 0.13), +0.10 (95% CI: 0.07, 0.14), and +0.13 (95% CI: 0.09, 0.16) higher cognitive, communication, and motor development z scores, respectively. The relation of weight-for-height z score (WHZ) was nonlinear with only wasted children (WHZ <−2) experiencing deficits ( P values for nonlinear relation < 0.05). Wasted children had −0.63 (95% CI: −0.97, −0.29), −0.32 (95% CI: −0.64, 0.01), and −0.54 (95% CI: −0.86, −0.23) z score deficits in cognitive, communication, and motor development z scores, respectively, relative to nonwasted children. Maternal stature and flush toilet use were associated with higher cognitive and motor z scores, whereas being born small for gestational age (SGA) was associated with a −0.16 (95% CI: −0.30, −0.01) z score deficit in cognition. Conclusions: Mild to severe chronic malnutrition was associated with increasing developmental deficits in Tanzanian children, whereas only wasted children exhibited developmental delays during acute malnutrition. Interventions to reduce SGA, improve sanitation, and increase maternal stature may have positive effects on child development. This trial was registered with the Australian New Zealand Clinical Trials Registry as ACTRN12610000636055.